Identifikasi dan Sebaran Hama Penggerek Batang Terhadap Pertumbuhan dan Produksi Tanaman Padi di Kecamatan Meurebo Aceh - Jasmi, Jasmi; Huri Afrina Dewi, Huri Afrina Dewi; Rosmerri, Rosmerri; Gunawan, Aristotel; Ansari, Leli Putri (Jurnal Pengabdian Agro and Marine Industry, 2024)
Rice is the main food crop in Indonesia, even Asia and the world. Rice is the main food source because the way it is cultivated and managed makes it a simpler food compared to other food crops. In efforts to increase rice productivity, there are still many obstacles, including the problem of pests, one of which is the stem borer pest in rice. The decline in rice production reached 1 -3% due to the stem borer pest [1]. The stem borer (Sciphopaga innotata) is a pest that attacks rice plants in the vegetative/tilling and generative phases. Moths or larvae suck food from rice stalks so that in the vegetative phase it inhibits the growth of tillers, while in the generative phase it inhibits the filling of the rice grains, resulting in empty and dry grains. This service activity was carried out in March 2024 in Mesjid Tuha village, Meurebo District, Aceh, using a survey method to identify stem borer pests descriptively based on existing references. The aim of this service activity is to find out and identify stem-boring pests in rice, based on the information obtained, this has been very detrimental to farmers